Michael Marker Dialogues with Francis on Primacy of Place: Advocating for Papaschase First Nation - Jarvis, Sharon (Journal of Contemporary Issues in Education)

(untitled) (University of Alberta, 2023)
This article begins from Michael Marker’s methodological invocation to center place and “theconsciousness of landscape” (2018, p. 453). The places at issue are manito sakahikan (aka Lac Ste. Anne, Alberta) and amiskwaciwaskahikan (aka Beaver Hills House of Edmonton, Alberta). Both places were in the news in 2022 when Pope Francis made his historic and tardy apology on behalf of the Catholic Church and its members for their role in the cultural genocide of the Indigenous Peoples of Canada. Both places hold spiritual significance for the Papaschase First Nation, whose traditional territory encompasses them, as well as for practicing Catholics. As a means of advocacy for the Papaschase First Nation, I trace the breaking of their treaty, in part, to the Church’s role in, and the dire consequences of, terra nullius and the Doctrine of Discovery. I contrast the Western view that one can own the land with a traditional Indigenous emphasis on the importance of sharing and caring with and for the land. I present my arguments via an imagined three-way dialogue among Dr. Michael Marker, Pope Francis, and myself. To create this dialogue, I draw on: Marker’s scholarly work, particularly on the primacy of place; Pope Francis’s homilies, statements, and earlier papal bulls (decrees). As a Métis from manito sakahikan, I share memories of the place of my ancestors and childhood that bring forth an Indigenous Métissage (Donald, 2009, 2012), underscoring place-based and sacred traditional relationships to “sentient landscapes” (Marker, 2018, p. 454). The dialogue takes place in three places: Ancient Gathering Places, At the Vatican, and An Imagined Place of Care and Share. The results of the conversation suggest the importance of an Indigenous perspective on the sacredness of place as a possible educational path toward a renewed future.